BLOCKCHAIN TECHNOLOGY INNOVATION AS AN OPTIMIZATION OF TRANSACTION SECURITY IN ISLAMIC FINANCIAL INSTITUTIONS - Nur Aisah; Siara Zazkia Juliana Putri; Muhammad Riza Hafizi (Journal of Central Banking Law and Institutions, 2025)
This study examines the role of blockchain technology in enhancing security within Islamic financial institutions, which adhere to Sharia principles emphasising transparency, fairness, and ethical conduct. The primary purpose is to explore blockchain’s potential to address financial risks and inefficiencies while ensuring compliance with Islamic values. Islamic financial institutions face challenges maintaining transaction security and transparency under Sharia constraints, especially as risks like fraud, manipulation, and operational inefficiencies persist. Blockchain’s decentralised ledger system offers solutions by ensuring immutable transaction records, real-time transparency, and secure cryptographic frameworks. Smart contracts further automate Sharia-compliant processes, reducing risks of non-compliance and fraud, while operational efficiencies are achieved through reduced costs and faster transaction processing. However, implementing blockchain in Sharia financial institutions faces limitations, including a lack of technical expertise, regulatory clarity, and inadequate infrastructure in many regions. These barriers highlight the need for capacity-building initiatives and robust regulations to support blockchain adoption in Islamic finance. The study emphasises blockchain’s transformative potential to revolutionise Islamic finance, fostering trust and operational excellence while overcoming current barriers through collaborative efforts. Further research is necessary to optimise blockchain’s integration into this sector.